Multifunctional PEEK implants via mussel adhesion-mediated assembly for osteoimmune regulation and antibacterial properties - Wang, Lei; Wang, Qiang; Wang, Fan; Xiong, Shouliang; Yang, Xin; Zhao, Jie; Lu, Xiao; Zhang, Yinchang; Chen, Pingbo; Qian, Surong; Lu, Guohai; Gu, Chengyong (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPolyetheretherketone (PEEK) is widely recognized for its exceptional mechanical properties and biocompatibility, making it a promising material for orthopedic implants. However, its inherent biological inertia—characterized by poor osteogenic potential, limited antibacterial activity, and excessive immune activation—compromises its clinical performance.MethodsTo address these limitations, we developed a multifunctional PEEK implant (PEEK-PDA-Sr/AMP) through a mussel-inspired self-assembly process, incorporating strontium ions (Sr2+) for dual biological functions and the antimicrobial peptide PMAP-36. A polydopamine (PDA) coating was first applied to enhance microscale surface roughness and hydrophilicity. Subsequently, Sr2+ and AMP were immobilized onto the PDA-modified surface.ResultsThe resulting PEEK-PDA-Sr/AMP implants significantly promoted the adhesion and spatial organization of bone marrow mesenchymal stem cells (BMSCs) and macrophages (BMMs) in vitro. Furthermore, the modified surface facilitated macrophage polarization toward a pro-regenerative phenotype, thereby fostering an osteoimmune microenvironment conducive to osteogenic differentiation of BMSCs. The functionalized implants also exhibited strong antibacterial efficacy against both Staphylococcus aureus and Escherichia coli. In a rat model of osteomyelitis, in vivo evaluations via micro-CT, histology, and immunohistochemistry confirmed that the PEEK-PDA-Sr/AMP implants markedly enhanced immunomodulation, bone regeneration, and osseointegration.DiscussionThis study demonstrates a novel surface bioengineering strategy for constructing multifunctional PEEK implants with improved immunomodulatory, osteogenic, and antibacterial properties, offering a promising solution to meet complex clinical requirements in orthopedic applications.